Spatial variation of the status of the retired population in Nineveh Governorate in 2021 - Fadel, Sultan Saeed (Journal of Tikrit University for Humanities, 2024)
The stage of retirement from work is one of the important life stages that a person goes through, which begins with childhood, then adolescence, youth, old age, and old age. Each of these stages has its own social, economic, and psychological problems. Studies of these stages have received many social researches and studies, including studies that I dealt with the retired population, because they spent these long years, which amount to more than 40 years, in serving the country and the people, and until he reached the retirement age of 63 years, and after reducing it, he became 60 years old. However, there are many problems that this retiree suffers from, including economic ones. Health, social, and psychological issues affect his family and social life. The salary may decrease and become insufficient with the rise in prices and annual inflation. Another section does not own a housing unit, which allocates part of its income to rent. The other section suffers from diseases, including chronic or aging diseases.